1980
DOI: 10.1159/000179117
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Cerebral Acetylcholinesterase Activity by Calcitonin: a Possible Mediation by 5-Hydroxytryptamine

Abstract: The stimulatory effect of calcitonin on cerebral acetylcholinesterase activity could not be observed in rats pretreated with p-chlorophenylalanine. The results suggest that the response of the enzyme activity to calcitonin is 5-hydroxytryptamine-mediated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Nevertheless, taken together, the obtained findings agree with the suggestion concern ing the involvement of brain serotonergic pathways in some central actions of calci tonins. In fact, it has been reported that a) the anorectic effect of sCT is strictly related to its ability to activate the serotonergic hypothalamic system (3), b) the analgesic activity of sCT involves a central serotonergic mechanism (9), and c) the stimulation of rat brain acetylcholinesterase activity induced by the porcine calcitonin is mediated by serotonin (10).…”
mentioning
confidence: 99%
“…Nevertheless, taken together, the obtained findings agree with the suggestion concern ing the involvement of brain serotonergic pathways in some central actions of calci tonins. In fact, it has been reported that a) the anorectic effect of sCT is strictly related to its ability to activate the serotonergic hypothalamic system (3), b) the analgesic activity of sCT involves a central serotonergic mechanism (9), and c) the stimulation of rat brain acetylcholinesterase activity induced by the porcine calcitonin is mediated by serotonin (10).…”
mentioning
confidence: 99%